Inquisitive semantics - Ciardelli, Ivano; Groenendijk, J. A. G. (Jeroen A. G.); Roelofsen, Floris (Oxford, United Kingdom Oxford University Press, 2019)
This book presents a new logical framework to capture the meaning of sentences in conversation. The traditional approach equates meaning with truth-conditions: to know the meaning of a sentence is to know under which circumstances it is true. The reason for this is that linguistic and philosophical investigations are usually carried out in a logical framework that was originally designed to characterize valid argumentation. However, argumentation is neither the sole, nor the primary function of language. One task that language more widely and ordinarily fulfils is to enable the exchange of information between conversational participants. In the framework outlined in this volume, inquisitive semantics, information exchange is seen as a process of raising and resolving issues. Inquisitive semantics provides a new formal notion of meaning, which makes it possible to model various concepts that are crucial for the analysis of linguistic information exchange in a more refined and more principled way than has been possible in previous frameworks. Importantly, it also allows an integrated treatment of statements and questions. The first part of the book presents the framework in detail, while the second demonstrates its benefits in the semantic analysis of questions, coordination, modals, conditionals, and intonation. The book will be of interest to researchers and students from advanced undergraduate level upwards in the fields of semantics, pragmatics, philosophy of language, and logic.
Includes bibliographical references and index.
Keywords: Semantics